Strategi Diversifikasi Mata Pencaharian Petani Kelapa Sawit di Kecamatan Teramang Jaya, Kabupaten Mukomuko, Indonesia: Livelihood Diversification Strategy Of Independent Oil Palm Farmers In Teramang Jaya, Mukomuko, Indonesia - Febriana, Ersa; Romdhon, Muhamad Mustopa; Trisusilo, Agung; Kilmanun, Juliana Carolina (Journal of Integrated Agribusiness, 2025)
This study aims to examine household livelihood assets, calculate household income from various income sources, and identify the livelihood strategies adopted by independent oil palm farmers in Teramang Jaya Subdistrict. The research employed a proportionate stratified random sampling method, involving 92 farmer households that met the selection criteria. Data were collected through observation, interviews, documentation, and structured questionnaires, and analyzed using both descriptive and quantitative approaches. The findings show that all households utilized five categories of livelihood assets: natural, human, physical, financial, and social. The average monthly income from on-farm activities was IDR 3,540,924, while off-farm activities contributed IDR 2,340,444. Non-farm income averaged IDR 3,414,462 per month. In terms of livelihood strategies, 3.26 percent of households engaged in livelihood intensification by optimizing other available land. A total of 98.91 percent of households adopted a dual livelihood strategy, which was the most effective in fulfilling household needs. In addition, 5.43 percent of households applied spatial or migration-based strategies as an alternative means of generating income.